A paramilitary retrieval team for accidental hypothermia. Insights gained from a simple classification with advanced treatment over 16 years in Denmark. (November 2020) - Kjaergaard, Benedict; Danielsen, Allan Vestergaard; Simonsen, Carsten; Wiberg, Sebastian
Abstract: Aim: To present the results from 16 years of nationwide cooperation between the Danish Airforce Search and Rescue Service and a Tertiary Heart Centre for the classification and treatment of accidental hypothermia. Methods: A mobile extracorporeal membrane oxygenation (ECMO) retrieval team was developed and could be contacted for nationwide advice and if indicated retrieval and/or treatment of patients by means of ambulance and/or helicopter. Accidental hypothermia was classified as mild, moderate, and severe, corresponding to awake, unconscious, and lifeless. The exact temperature was not considered relevant in the primary assessment. The mild group was treated with blankets and minimal invasive with warm i.v. infusions. The moderate group was primarily treated with an ABC approach, and if circulation was unstable due to arrhythmias or bleeding, invasive warming was performed with pleural lavage under ECMO preparedness. The severe group was treated with CPR followed by ECMO. All patients were examined for underlying disorders. Results: The team was involved in 204 patients, but for 47 patients treatment was stopped as they were considered beyond therapeutic reach, leaving 157 treated patients with 108 (69%) survivors. Among 54 ECMO patients, 21 (39%) survived to hospital discharge. Conclusions: We successfully implemented a simplified classification of accidental hypothermia and initiated a nationwide cooperation for retrieval and/or treatment of accidental hypothermic patients.